INSTITUTIONAL MECHANISM FOR IMPLEMENTING STATE INFORMATION POLICY IN THE CONDITIONS OF DIGITAL TRANSFORMATION - DUBOVYK, Denis (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article carries out a comprehensive study of the institutional mechanism for implementing state information policy in the context of digital transformation, which fundamentally changes approaches to public administration, communication and interaction of the state with civil society. The evolution of theoretical approaches to the institutional analysis of information policy is considered, the importance of institutional stability as a key prerequisite for the effective functioning of the state administration system in the context of dynamic socio-political and technological changes is substantiated. The content and structure of the institutional mechanism for implementing state information policy are determined, which includes regulatory and legal support, the system of state authorities, mechanisms of interinstitutional coordination, digital tools for managing information flows and channels of strategic communications. The impact of digitalization on the transformation of traditional management models is analyzed, in particular, the transition from hierarchical forms of information influence to network and interactive models of state communication. Particular attention is paid to the current challenges of implementing state information policy, including threats to information security, the spread of disinformation, the fragmentation of regulatory and legal regulation, the insufficient level of digital competence of officials and unequal access of citizens to digital resources. The peculiarities of the functioning of the institutional mechanism in conditions of martial law, when information policy acquires strategic importance for ensuring national security and social stability, are highlighted. The need to adapt the state information policy of Ukraine to European standards in the context of European integration processes, the development of digital governance and the formation of a positive state brand is substantiated. It is concluded that an effective institutional mechanism for implementing state information policy should be based on the principles of transparency, openness, inter-sectoral interaction and technological innovation, and also be focused on strengthening citizens’ trust in state institutions in the digital information space.